SHORT FILM ADVERTISING CREATIVE STRATEGY IN POSTMODERN ERA WITHIN SOFTWARE VIDEO EDITING - Nur Kholisoh; Dicky Andika; Suhendra Suhendra (Bricolage : Jurnal Magister Ilmu Komunikasi, 2021)
The evolution of integrated communication has given many opportunities for advertisers to market their products through internet, one of which is to make advertisements prepared in the form of short film advertising. Autodesk® Inc as one of the foremost producers of video editing software in America uses short film advertising entitled “Fix It In Post” as the form of its marketing communication media. The short film advertising “Fix It In Post” uses iconic signs in communicating its products through USP - Unique Selling Proposition creative strategy. The objective of this research is to find signs visualized as a description of the sophistication of software video editing, and to impart brand image to Autodesk® Smoke® as a sophisticated brand software video editing. Based on the result of research a Semiotics of of the Cinema Christian Metz analysis, it was found out that there were signs visualized to describe the sophistication of software video editing namely various features used by the video editor. Each feature of software describing such sophistication is represented in a series of scene forming a sequence, so that it can convey a brand image to the Autodesk® Smoke® as a sophisticated brand software video editing.